Pengaruh Fasilitas Kerja Dan Lingkungan Kerja Non Fisik Terhadap Kinerja Pegawai Pada Dinas Peternakan Dan Kesehatan Hewan Kabupaten Bima - Era Wati; Mulyadin Mulyadin (Universitas 45 Surabaya, 2023)
Human resources are an important factor for the success of an institution or organization because humans are living assets that need to be maintained and developed. Therefore, employees must receive special attention from the institution or organization which must be managed well so that the efficiency and effectiveness of the organization will increase. This is intended so that the human resources owned by the organization are able to provide optimal contributions in efforts to achieve organizational goals. In managing human resources, management is needed that is able to manage resources in a planned and systematic manner. One of the things that should be the main concern for human resources leaders is the work facility system and non-physical work environment on employee performance.